Examining Adolescent Identity Formation Processes in Immersion Semester High Schools. Issue 2 (3rd April 2022) - Meerts-Brandsma, Lisa; Sibthorp, Jim
ABSTRACT: The study investigated four aims that focused on the relationship between immersion semester high schools, identity formation processes, and contextual factors. Participants included students attending an immersion semester high school and students in a waitlist comparison group who would attend an immersion semester high school. Both groups completed a Pre/Post Semester Survey that assessed identity formation processes (using the Dimensions of Identity Development Scale, DIDS) and contextual variables, and Daily Activity Surveys that assessed how much a student thought about their values and beliefs and the presence of contextual variables in identified daily activities. We found that students at immersion semester high schools reported significant increases in the intensity of their identity formation processes in contrast to the waitlist comparison group, and that the context at immersion semester high schools differed significantly from the context for the waitlist comparison group. Students at immersion semester high schools thought significantly more about their values and beliefs, and regardless of group, thinking about one's values and beliefs was related to contextual factors, such as the role of the teacher, sense of belonging, opportunities for reflection, and the meaningfulness of the experience.